Comparing the backfilling of mesoporous titania thin films with hole conductors of different sizes sharing the same mass density. (2020) - Markl, Raphael S.; Hohn, Nuri; Hupf, Emanuel; Bießmann, Lorenz; Korstgens, Volker; Kreuzer, Lucas P.
No abstract available